Primary education in India: Prospects of meeting the MDG target - Sonia Bhalotra; Bernarda Zamora (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper uses two large repeated cross-sections, one for the early 1990s, and one for the late 1990s, to describe growth in school enrolment and completion rates for boys and girls in India, and to explore the extent to which enrolment and completion rates have grown over time. It decomposes this growth into a component due to changes in the characteristics that determine schooling, and another associated with changes in the responsiveness of schooling to given characteristics. Our results caution against the common practice of using current data to make future projections on the assumption that the model parameters are stable. The analysis nevertheless performs illustrative simulations relevant to the question of whether India will be able to achieve the Millennium Development Goal of realising universal primary education by the year 2015. The simulations suggest that India will achieve universal attendance, but that primary school completion rates will not exhibit much progress.
Keywords: I21; I31; O12; C25; 330; Millennium Development Goals; primary schooling; attendance; completion rates; gender; India; decomposition; Allgemeinbildende Schule; Indien; Millennium Development Goals